Nuclear calcium signaling - Gerasimenko, Oleg; Gerasimenko, Julia (Henry Stewart Talks, 2007)
Nuclear calcium signaling, an intriguing history of the last 10 years of research and promising recent developments with the emphasis on fluorescent confocal techniques, Basic features and major consensus on principles, Uncertainty about nuclear calcium independence, New data on the elusive NAADP receptor